DNA computing and molecular programming 17th international conference, DNA 17, Pasadena, CA, USA, September 19-23, 2011. proceedings - Cardelli, Luca; Shih, William (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 17th International Conference on DNA Computing and Molecular Programming, DNA17, held in Pasadena, CA, USA, in September 2011. The 12 revised full papers presented together with 5 invited talks were carefully selected from numerous submissions. Research in DNA computing and molecular programming draws together mathematics, computer science, physics, chemistry, biology, and nanotechnology to address the analysis, design, and synthesis of information-based molecular systems. This annual meeting is the premier forum where scientists with diverse backgrounds come together with the common purpose of advancing the engineering and science of biology and chemistry from the point of view of computer science, physics, and mathematics.